Nucleophilic fluoroalkylation/cyclization route to fluorinated phthalides - Inaba, Masanori; Sakai, Tatsuya; Shinada, Shun; Sugiishi, Tsuyuka; Nishina, Yuta; Shibata, Norio; Amii, Hideki (Beilstein Journal of Organic Chemistry, 2018)
Discribed in this article is a versatile and practical method for the synthesis of C3-perfluoroalkyl-substituted phthalides in a one-pot manner. Upon treatment of KF or triethylamine, 2-cyanobenzaldehyde reacted with (perfluoroalkyl)trimethylsilanes via nucleophilic addition and subsequent intramolecular cyclization to give perfluoroalkylphthalides in good yields.
Keywords: cyclization; fluorine; lactone; phthalide; trifluoromethylation